Some aspects of the transport system of iron metabolism depending on the degree of iron overload syndrome in children with chronic hepatitis B - F. I. Inoyatova; Kh. M. Kadyrkhodjaeva; G. Z. Inogamova; A. Kh. Akhmedova; N. K. Valieva; F. G. Abdullaeva; N. A. Ikramova (Детские инфекции (Москва), 2019)
Objective: to study the status of markers of the transport system of iron metabolism and the marker profile of HBV infection, depending on the degree of iron overload syndrome in children with chronic hepatitis B.The object of the study were 1 85 children with HBV with iron overload syndrome, aged 4—18 years. Specific research methods included determination by ELISA: sTfR (soluble transferrin receptors), FR (ferritin), FPN (ferroportin), HEPH (hefestin), TfR-2 (transferrin-2 receptors) and serum active Hepcidin-25 (HPS) blood. Viro-logical verification was performed by ELISA and PCR: HBsAg, HBsAb, HBeAg, HBeAb, total HBcorAb, HCVAb, HDVAb, HBV-DNA.A directly proportional dependence of the FPN level and an inversely proportional dependence of the level of HEPH/TfR-2 on the degree of iron overload syndrome were revealed — the higher the presentability of hemosiderosis, the higher the expression of FPN and the suppression of HEPH/TfR-2 with the consequence of decreased transcription of hepcidin-25 in hepatocytes. Confirmation of this fact served as the severity of HBV activity, which correlated with the degree of iron overload syndrome, the lower the transferrin saturation ratio, the higher the viral aggression, which we interpreted as an unfavorable factor in terms of the prognosis of the disease.